Diet quality is associated with adipose tissue and muscle mass: the Coronary Artery Risk Development in Young Adults (CARDIA) study - Masoud Isanejad; Lyn M. Steffen; James G. Terry; James M. Shikany; Xia Zhou; So‐YunYi; David R. Jacobs Jr; John Jeffrey Carr; Brian T. Steffen (Wiley, 2024)
Abstract Background Aging is associated with changes in body composition, and preventing loss of muscle mass and accumulation of excess adipose tissue in middle‐aged adults may reduce age‐related conditions at older ages. Dietary intake is one lifestyle factor shown to improve or maintain body composition. However, few studies have examined the Healthy Eating Index2015 (HEI2015), a measure of diet quality, and the association with body composition in adult men and women. Methods Participant data (n = 3017) from the Coronary Artery Risk Development in Young Adults (CARDIA) study were used to examine the associations of the HEI2015 with body composition measures at Year 25 (Y25), including (1) 25 year‐change in weight, body mass index (BMI), and waist circumference and (2) a computed tomography (CT) scan at Y25 measured muscle mass, muscle quality (better quality = less lipid within the muscle), and adipose tissue depots visceral adipose tissue (VAT), subcutaneous adipose tissue (SAT), and adipose within skeletal muscle (intermuscular adipose tissue; IMAT). Dietary intake was assessed by a diet history three times over 20 years, at years 0, 7, and 20. HEI2015, averaged over three exams, was created and categorized into quintiles. Multiple regression analysis evaluated the associations of body composition stratified across quintiles of HEI2015 adjusted for demographic characteristics, energy intake, lifestyle factors, and baseline anthropometric measures as appropriate. Race-sex interaction was tested (Pinteraction > 0.30). Results Over 25 years of follow‐up, averaged HEI2015 was significantly and inversely associated with weight gain (Quintile 1 (Q1) 37.3 lb vs. 32.9 in Q5; Ptrend = 0.01), change in BMI (Q1 5.8 kg/m2 vs. 5.0 in Q5; Ptrend = 0.005), and change in waist circumference (Q1 17.5 cm vs. 15.2 cm in Q5; Ptrend < 0.001). By Y25, HEI2015 was inversely associated with VAT Q1 136.8 cm3 vs. 116.6 in Q5; Ptrend < 0.001) and IMAT volumes (Q1 9.52 vs. 8.12 cm3 in Q5; Ptrend < 0.001). Although total muscle volume declined (Ptrend = 0.03), lean muscle mass volume was similar across quintiles (Ptrend = 0.55). The IMAT/total muscle mass ratio declined across HEI2015 quintiles (Ptrend < 0.001). Finally, higher HEI2015 was associated with better muscle quality at Y25 (higher value = less lipid within the muscle; Q1 41.1 vs. 42.2 HU in Q5; Ptrend = 0.002). HEI2015 was nonlinearly, but inversely, associated with SAT (nonlinear P = 0.011). Conclusions Improving diet quality in young to middle‐aged adults is a recommended strategy to promote better measures of body composition. Our study findings suggest that healthier food choices may influence body composition.